The Dynamic of Extracellular Vesicles in Patients With Subacute Stroke: Results of the “Biomarkers and Perfusion—Training-Induced Changes After Stroke” (BAPTISe) Study - Jödicke, Ruben A.; Huo, Shufan; Kränkel, Nicolle; Piper, Sophie K.; Ebinger, Martin; Landmesser, Ulf; Flöel, Agnes; Endres, Matthias; Nave, Alexander H. (Frontiers in Neurology, 2021)
Objective: Extracellular vesicles (EV) are sub-1µm bilayer lipid coated particles and have been shown play a role in long-term cardiovascular outcome after ischemic stroke. However, the dynamic change of EV after stroke and their implications for functional outcome have not yet been elucidated. Methods: Serial blood samples from 110 subacute ischemic stroke patients enrolled in the prospective BAPTISe study were analyzed. All patients participated in the PHYS-STROKE trial and received four-week aerobic training or relaxation sessions. Levels of endothelial-derived (EnV:AnnexinV+,CD45-,CD41-,CD31+/CD144+/CD146+), leukocyte-derived (LV:AnnexinV+,CD45+,CD41-), monocytic-derived (MoV:AnnexinV+,CD41-,CD14+), neuronal-derived (NV:AnnexinV+,CD41-,CD45-,CD31-,CD144-,CD146-,CD56+/CD171+/CD271+), and platelet-derived (PV:AnnexinV+, CD41+) EV were assessed via fluorescence activated cell sorting before and after the trial intervention. The levels of EV at baseline were dichotomized at the 75th percentile, with the EV levels at baseline above the 75th percentile classified as “high” otherwise as “low”. The dynamic of EV was classified based on the difference between baseline and post intervention, defining increases above the 75th percentile as “high increase” otherwise as “low increase”. Associations of baseline levels and change in EV concentrations with Barthel-Index (BI) and cardiovascular events in the first 6 months post-stroke were analyzed using mixed model regression analyses and cox regression. Results: Both before and after intervention PV formed the largest population of vesicles followed by NV and EnV. In mixed-model regression analyses, low NV (-8.57[-15.53,-1.57;95%CI]) and low PV (-6.97[-13.92,-0.01;95%CI] at baseline were associated with lower BI in the first 6 months post-stroke. Patients with low increase in NV (8.69[2.08,15.34;95%CI]) and LV (6.82[0.25,13.4;95%CI]) were associated with reduced BI in the first 6 months post-stroke. Neither baseline vesicles nor their dynamic were associated with recurrent cardiovascular events. Conclusion: This is the first report analyzing the concentration and the dynamic of EV regarding associations with functional outcome in patients with subacute stroke. Lower levels of PV and NV at baseline were associated with a worse functional outcome in the first 6 months post-stroke. Furthermore, an increase in NV and LV over time were associated with worse BI in the first 6 months post-stroke. Further investigation of the relationship between EV and their dynamic with functional outcome post-stroke are warranted. Trial registration: NCT01954797